Protected Areas and Rural Depopulation in Spain: A Multi-Stakeholder Perceptual Study - Rodriguez-Rodriguez, David; Larrubia-Vargas, Remedios (IOAP-MPDI, 2022)
Protected areas (PAs) are thought by some to contribute to local wellbeing and socioeconomic development, whereas for others PAs remain a regulatory burden that hampers rural development. Here, we sought to ascertain the perceived causes of rural depopulation and the potential impact of four Natura 2000 sites on the wellbeing and depopulation figures of four protected rural municipalities in Spain that were selected as extreme case studies. We used phone surveys to elicit experts’ views (n = 19) on the topic and convened eight in-person workshops to garner local residents’ insights (n = 40) using structured questionnaires. We complemented perceived wellbeing data from PAs with surveys to residents in neighbouring unprotected municipalities (n = 28). Both experts and workshops’ attendees from protected municipalities overwhelmingly attributed depopulation figures to structural causes linked to transport accessibility, basic service provision and the existence of job opportunities, which they perceived to be unrelated to the PAs’ regulations or management. Local residents did generally not perceive any impact on their collective or individual wellbeing from those PAs, and most who did, expressed a negative impact chiefly due to socioeconomic restrictions. Four-fifths of the experts and half of the workshops’ attendees from protected municipalities, however, expressed that PAs’ administrations could help improve depopulation figures in their towns mainly through promoting tourism and greater compatibility of land uses, including housing and infrastructure development. While the assessed Natura 2000 sites certainly have scope for tourism promotion, their lenient legal regimes make it largely unfeasible to broaden land use compatibility without damaging protected features
Keywords: Impacto; Natura 2000; Impact; Resident; Expert; Opinion; Wellbeing; Case study